RANCANG BANGUN SISTEM INFORMASI E-LEARNING PADA SMK PGRI 37 JAKARTA - Evy Priyanti; Rahmad Budi Ansyah; Fachrul Ramadhani; Huzaiful Yaman (Universitas Bina Sarana Informatika Kota Sukabumi, 2020)
Based on Permendikbud No. 60 of 2014 states that the implementation of PRAKERIN using a block system is carried out for half a semester around 3 months, with this enormous amount of time making students lacking in teaching and learning in class. Therefore it is very necessary methods that can support the education system that can facilitate students in learning, one of them with e-learning systems. This system can help students in learning and also greatly help the teaching board in developing material because e-learning methods can be opened with more free time. Some subjects can be made e-learning systems so that students have more time to learn and develop the knowledge they have. E-learning at SMK PGRI 37 Jakarta makes students progress in learning lessons that cannot be learned in class because of the limited time available. E-learning systems can be developed to the maximum in accordance with the changing times due to the sophistication of technology that can facilitate human work at this time. E-learning at SMK PGRI 37 Jakarta is one of the breakthroughs that utilizes technology for the development of students' abilities and development.